Pengaruh Financial Literacy dan Risk Perception terhadap Keputusan Investasi Saham Syariah pada Mahasiswa FEBI UINSU - Sabrina, Zafira; Marliyah, Marliyah; Harahap, Muhammad Ikhsan (ITB AAS INDONESIA Surakarta, 2024)
This study employs a descriptive qualitative research method. It was conducted directly on the Psychologically, students have emotional maturity in managing their finances, preparing investment plans, but are not necessarily more precise in making decisions, even though they have a fairly good understanding of finances. Thus, if students as investors want to improve their investment decisions, then students need to increase their financial literacy and risk perception, conversely if students do not increase their financial literacy and risk perception, then their investment decisions will be low. This article aims to analyze the influence of financial literacy and risk perception on sharia investment decisions of students at the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. The sample for this research was 71 respondents. This article uses quantitative methods and data is collected through distributing questionnaires. The analysis method uses validity, reliability, hypothesis testing, and multiple linear regression analysis. The analysis findings show that financial literacy has a significant influence on sharia investment decisions, risk perception has a significant influence on sharia investment decisions. Financial literacy and risk perception simultaneously have a significant influence on sharia investment decisions of students at the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra.